Respon Penawaran Karet Alam Indonesia - Zahari Zen; Mas Soedjono; Gunawan Sumodiningrat (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1988)
Respon Penawaran Karet Alam Indonesia